Implementasi Pembelajaran Berdiferensiasi untuk Meningkatkan Hasil Belajar Siswa - Afdal Yusra; Oriza Candra (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
A common problem in learning is the low achievement of students, which is influenced by differences in students’ understanding and learning styles, as well as the insufficient application of innovative and student-centered learning models. Therefore, an instructional approach that can address these issues is needed, such as differentiated learning combined with the Problem Based Learning (PBL) model. This study employed a quantitative approach using an experimental method with a One-Group Pretest-Posttest Design. The research subjects were tenth-grade students of the Electrical Installation Engineering program at SMK N 2 Sawahlunto. Data collection was conducted using pretest and posttest instruments to assess students’ learning outcomes. The data obtained were analyzed using N-Gain scores and classical completeness. The results indicate that the implementation of differentiated learning integrated with the PBL model is quite effective in improving students’ learning outcomes. This is evidenced by an increase in the average posttest score to 86.06 from a pretest score of 59.66. The implementation of differentiated learning was proven to significantly enhance students’ learning achievement, as reflected by a normalized gain score of 0.66, which falls into the medium category, with a classical completeness of 97%.